Characteristics and properties of food - O'Sullivan, Gerardine; Video Educational Australia (Australia : Video Educational Australia, 1996)
This program list food compounds as well as factors causing changes in food composition. part 2 focus on the role that enzymes play in the ripening and deterioration of fruit juice and the liquidation of the soft centres in chocolates, the properties of pectin are demonstrated in the process of making jam and the pigments in different groups of fruits and vegetables in order to better preserve their colour and appeal
Part 2. Enzymes, pectin and pigments
Title from title screen
Executive producer, Terry Guthridge ; camera operator/sound, Steve Welch ; graphics, Roy Hosmick ; editors, Republic films, Rowan Webb, Estelle McGechie
Narrator: Justin Shortal
Keywords: Food -- Composition; Food consumption -- Health aspects; Nutrition; Health